Treatment outcomes in cavitary multidrug-resistant/rifampicin-resistant tuberculosis and risk factors for cavity closure: a retrospective cohort study in Southwest China - Qing Chen; Liping Zou; Xianzhen Tang; Tao Huang; Zhouli Guo; Jiying Sun; Xiaoli Lu; Shenjie Tang; Guihui Wu; Wei He (Scientific Reports)
Abstract Pulmonary cavities in patients with tuberculosis contribute to antibiotic failure, transmission, morbidity, and mortality. We aimed to report the treatment outcomes and risk factors for cavity closure in cavitary multidrug-resistant/rifampicin-resistant tuberculosis in Southwest China. This study was a retrospective cohort study which included adult patients with multidrug-resistant /rifampicin-resistant tuberculosis in Southwest China from January 2018 to January 2023. The patients were categorized into cavity and non-cavity groups, and their clinical characteristics and treatment outcomes were retrospectively compared. A logistic regression model was used to identify potential risk factors associated with cavity closure. In this study, 305 patients were enrolled, with 223 cases in the cavity group and 82 cases in the non-cavity group. The median age of patients in the cavity group was 31 (24, 44) years, with a male to female sex ratio of 155/68. Within the cavity group, 8.1% of patients had rifampicin-resistant tuberculosis, 49.8% had multidrug-resistant tuberculosis, and 42.2% had pre-extensively-drug resistant tuberculosis. The treatment outcomes of the cavitary group showed that 48.9% of patients were cured, 28.3% completed treatment, 14.8% were lost to follow-up, and 6.7% could not be evaluated, with one failure and two deaths. Various factors such as male gender, smoking, drinking, tuberculosis treatment history, baseline AFB smear, bilateral disease, and specific symptoms were more prevalent in the cavity group compared to the non-cavity group. Sputum culture conversion rates at 2 and 6 months were lower in the cavity group (25.6% vs 37.8%; 63.7% vs 79.3% ,all P < 0.05). Within patients with cavities, 40.6% experienced cavity closure after treatment, with a median closure time of 9.00 months. Baseline CD3 + T cell counts decreased was found to be an independent risk factor for cavity closure (aOR = 2.278, 95% CI 1.109–4.680, P = 0.025), while the use of a bedaquiline-containing regimen (aOR = 0.305, 95% CI 0.140–0.663, P = 0.003) and a delamanid-containing regimen (aOR = 0.260, 95% CI 0.086–0.785, P = 0.017) were protective factors. Cavities may influence the timing of culture conversion rather than influencing the treatment outcomes in patients with MDR/RR-TB. The use of bedaquiline and delamanid in treatment regimens for MDR/RR-TB patients could promote cavity closure and may enhance the management of cavitary MDR/RR-TB. Furthermore, the enhancement of immunotherapy could potentially contribute to reducing the burden of cavitary MDR/RR-TB.